Pembuatan Tinta Spidol dari Pelepah Kelapa Sawit dengan Variasi Jenis dan Konsentrasi Bahan Perekat - Jepryanto Hutasoit; Maria Ulfah; Adi Ruswanto (Program Studi Teknologi Hasil Pertanian, 2023)
Marker ink dyes are generally made from synthetic materials, including anthraquinone which is corrosive and causes irritation to the skin. It is hoped that the marker ink dye from palm frond fiber can overcome this problem. Ink made from carbon fiber from palm fronds to be able to stick to a whiteboard requires adhesive materials including gum arabic, tapioca flour and porang flour. This research aimed to determine the effect of the type and amount of adhesive on the physical and organoleptic properties of marker ink from palm frond carbon produced, as well as to obtain the type of adhesive and amount of adhesive that is capable of producing good marker ink. This research was designed using a Randomized Complete Block Design (RCBD) with two variable factors. The first factor is the comparison of adhesive types (A) with 3 levels, including: A1 (gum arabic), A2 (tapioca flour), A3 (porang flour). The second factor is the amount of adhesive (B) with 3 levels, including: B1 (10%), B2 (20%), B3 (30%). The results showed that the type of adhesive had an effect on density, viscosity, light intensity and adhesion, but had no effect on color preference, ease of removal and odor preference. The amount of adhesive affects density, viscosity, light intensity and adhesion, but does not affect color preference, ease of removal and odor preference. The best ink was obtained from A1B1 treatment with an average consumer acceptance value of 3.80 (like), density 0.94 g/m3, viscosity 15.60 cP, light intensity 0.23 lux, adhesion 13.01%.